"Top-down" Does Not Mean "Voluntary". Issue 1 (14th May 2018) - Gaspelin, Nicholas; Luck, Steven J.
Attention researchers have long debated the roles of top-down and bottom-up mechanisms in controlling attention. Theeuwes (2018 ) has argued that that top-down control is much less common than typically assumed and that a third mechanism—selection history—plays an underappreciated role in guiding visual attention. Although Theeuwes has made a strong case for the importance of selection history, his arguments for a limited role of top-down mechanisms involve conflating the terms "top-down" and "voluntary." Cognitive psychologists typically use the term "top-down" processing to refer to any perceptual phenomenon that is influenced by context, learning, or expectation, which would include selection history. This highlights a broad problem in attention capture research: The terms used to describe attentional control are often poorly defined, and much current debate seems to be related to the meaning of words. To move forward in understanding the actual mechanisms of attentional control, we must agree on what terms such as "top-down" and "bottom-up" actually mean.